Wątki emancypacyjne w biegu życia osoby stopniowo tracącej wzrok - Czerwińska, Kornelia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The first part of the article consists of a review of theoretical literature concerning such issues as: a basic rationale of the emancipation paradigm in general and special education; interdependencies among the ideas of autonomy, empowerment and emancipation in selected pedagogical approaches; and a specific character of oppression resulting from gradual loss of sight. The second part of the text is a case study presenting selected emancipation threads in the life of a newly blinded person. The presented case is an example of shaping one‟s own life and consciously working on self-empowerment.